Magnesium in pain control - mechanisms of action in perioperative pain, neuropathic pain and migraine - Konarska, Anna; Fabijański, Artur; Dukacz, Adriana; Firlej, Wojciech; Rychlewska-Duda, Joanna; Lisiecka, Justyna; Nowak, Michał; Janik, Mateusz; Ufnalska, Barbara; Machowiak, Anna (Journal of Education, Health and Sport, 2025)
Introduction Magnesium is a crucial macroelement with widespread effects on the nervous and muscular systems.. Due to its role as an NMDA receptor antagonist, magnesium has garnered significant attention in pain management research, particularly for its potential to modulate both acute and chronic pain. This article provides an overview of magnesium’s therapeutic applications in neuropathic pain, migraine, and perioperative pain, drawing on research from PubMed and Google Scholar published between 1988 and 2025. Aim of study This review aims to present the state of knowledge about magnesium’s possible role in pain control and present mechanism of its influence on the nociceptive stimuli reception. Materials and methods Publication research was made using databases PubMed and Google Scholar. Keywords used in research were among others: magnesium, pain, neuropathic pain, migraine, perioperative pain, magnesium deficiency. Current state of knowledge Magnesium plays a crucial role in the management of various pain conditions, including perioperative, neuropathic, and migraine pain, through its multifactorial mechanisms. These include NMDA receptor antagonism, calcium channel blockade, anti-inflammatory effects, and muscle relaxation, all of which contribute to its analgesic properties. Evidence suggests that magnesium supplementation can reduce opioid use, counteract central and peripheral sensitization, and potentially prevent migraine attacks, highlighting its potential as an effective adjuvant in pain management strategies. Summary (Conclusions): Magnesium offers significant therapeutic potential in managing perioperative, neuropathic, and migraine pain through mechanisms such as NMDA receptor antagonism, calcium channel blockade, and neuroinflammation modulation. Its use can reduce opioid consumption, enhance pain relief, and improve outcomes, highlighting the need for further research into its clinical applications in pain management.